PELATIHAN SIKLUS AKUNTANSI UNTUK SISWA/I SMA KRISTOFORUS I JAKARTA - Wijoyo, Amin; Sari, Vinnetta Ratna; Patricia, Virginia; Lie, Irene Kim; Widjaja, Karen (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
This teaching assistance or training activity has a positive aim for Santo Kristoforus 1 High School students who have limitations in understanding accounting material. In this teaching assistance, the author provides and explains an understanding of the Ledger, Trial Balance and Working Papers to students at Santo Kristoforus 1 High School to deepen their insights towards the materials. This teaching assistance or accounting material training activity is held face to face or offline for students in grades 10, 11 and 12. The UNTAR PKM team carries out this teaching activity twice a week, namely on Wednesdays for students in grades 11 and 12, as well as on Fridays for grade 10. From the training that has been carried out, it can be concluded that the students of Santo Kristoforus 1 High School have understood the material presented by the UNTAR PKM Team, as seen from the students' activeness in completing the practice questions given and the game sessions that were held. Through this training, it is hoped that it will be useful for Santo Kristoforus 1 High School students who want to continue their studies at university. Kegiatan asistensi mengajar atau pelatihan ini memiliki tujuan yang positif bagi siswa/i SMA Santo Kristoforus 1 yang memiliki keterbatasan dalam pemahaman terhadap materi akuntansi. Dalam asistensi mengajar ini, penulis memberikan dan menjelaskan mengenai pemahaman mengenai Buku Besar, Neraca Saldo, dan Kertas Kerja kepada siswa/i SMA Santo Kristoforus 1 agar memiliki wawasan yang lebih mendalam mengenai materi tersebut. Kegiatan asistensi mengajar atau pelatihan materi akuntansi ini diselenggarakan secara tatap muka atau secara offline untuk siswa/i yang berada di kelas 10, 11, dan 12. Tim PKM UNTAR melakukan kegiatan mengajar ini sebanyak dua kali dalam satu minggu, yaitu di hari Rabu bagi siswa/i kelas 11 dan 12, serta di hari Jumat untuk kelas 10. Dari pelatihan yang sudah dilaksanakan dapat disimpulkan siswa/i SMA Santo Kristoforus 1 telah memahami materi yang sudah dipaparkan oleh Tim PKM UNTAR, terlihat dari keaktifan siswa/i dalam menyelesaikan latihan soal yang diberikan dan permainan yang telah dirancang. Pelatihan ini diharapkan dapat berguna bagi siswa/i SMA Santo Kristoforus 1 yang ingin melanjutkan studi mereka di perguruan tinggi.